Investment in the Sports Sector: Is Legislation a Bottleneck? - Abderrahim Rharib; Amina Azmi (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Since 2008 and following the royal directives in the letter addressed to the participants of the sports conference in Skhirat, major efforts have been made to promote mass and spectator sports practice in order to improve the sporting landscape and to solve problems related to financing sports. On the legislative side, there has been the promulgation of a law on physical education and sport, another on anti-doping and a third proposing measures to combat violence and vandalism during spectator sport. Laws were also to contribute to this dynamism through certain tax amendments intended to promote the professionalism of sport. However, an in-depth analysis of the legislation governing the sports sector reveals several factors which must be addressed by the legislator in order to remedy thesituation. These factors can seriously impede investment and wealth creation initiatives in this sector.
Keywords: 650; Sport; Investment; Funding; Legislation